Safe enough? : a history of nuclear power and accident risk - Wellock, Thomas Raymond (University of California Press, 2021)
"Since the dawn of the Atomic Age, nuclear experts have labored to imagine the unimaginable and prevent it. They confronted a deceptively simple question: when is a reactor "safe enough" to adequately protect the public from catastrophe? Some experts sought a deceptively simple answer: an estimate that the odds of a major accident were, literally, a million to one. Far from simple, this search to quantify accident risk proved to be a tremendously complex and controversial endeavor, one that altered the very notion of safety in nuclear power and beyond. Safe Enough? is the first history to trace these contentious efforts, following the Atomic Energy Commission and the Nuclear Regulatory Commission as their experts experimented with tools to quantify accident risk for use in regulation and to persuade the public of nuclear power's safety. The intense conflict over risk assessment's value offers a window on the history of the nuclear safety debate and the beliefs of its advocates and opponents. Across seven decades and the accidents at Three Mile Island, Chernobyl, and Fukushima, the quantification of risk has transformed society's understanding of the hazards posed by complex technologies, and what it takes to make them safe enough"--